Modulation of homologous recombination gene activity in breast tumor cells in an in vitro model - M. M. Tsyganov; A. A. Frolova; E. A. Kravtsova; I. A. Tsydenova; M. K. Ibragimova (Успехи молекулярной онкологии, 2024)
Introduction. It has been established that the presence of homologous recombination deficiency in a breast tumor is associated with the effectiveness of treatment. But despite the high chemosensitivity of the tumor to DNA-damaging agents, complete pathological responses to treatment are very rare. And this process may be based on a change in the somatic status of BRCA1, that is, a reversion and return of the wild-type allele occurs and the DNA repair function is restored.Aim. To evaluate changes in the presence of chromosomal aberrations and the expression profile of the main genes of homologous recombination in cell models of breast cancer under the influence of cisplatin and docetaxel.Materials and methods. The study was conducted on breast cancer tumor cell cultures: MCF-7, MDA-MB-231 and MDA-MB-468. A cell model of drug resistance was obtained for two drugs: cisplatin and docetaxel. RNA and DNA were isolated from cell suspension using the RNeasy Plus Mini Kit and QIAamp DNA Mini Kit (Qiagen, Germany), respectively. The expression level of homologous recombination genes was assessed using reverse transcription polymerase chain reaction. To assess the presence of chromosomal aberrations, microarray analysis was performed on DNA chips.Results. Restoration of normal copy number for the BRCA1, CDK12, CHEK1 and RAD51D genes in MCF-7 under the influence of cisplatin was shown. For BRCA2 and PALB2, amplifications were detected. A statistically significant increase in the expression of the BRCA1 (p = 0.04), BRCA2 (p = 0.02), PALB2 (p = 0.01) and RAD51D (p = 0.05) genes was also shown. MDAMB-231 shows that all identified loci with deletions, where the BRCA2, BARD1, CHEK2, PALB2 and RAD54L genes are localized, are restored to normal copy number by cisplatin. The appearance of amplifications was registered for BRCA1, BRIP1, FANCL, RAD51B, PARP1. A similar result was shown for docetaxel. An increase in the expression level is typical for the genes BRCA1 (p = 0.02), BRCA2 (p = 0.02), CHEK2 (p = 0.05), FANCL (p = 0.04), PALB2 (p = 0.05), RAD51C (p = 0.02), PARP1 (p = 0.02), which corresponds to the appearance of amplifications. In the MDA-MB-468 cell culture, an increase in the copy number of only the BRCA1 gene is observed. The effect of docetaxel has no effect on this cell culture. The level of BRCA1 expression increases in direct proportion to the duration of drug action.Conclusion. Thus, the study showed that under the influence of cisplatin, reversion of not only homologous recombination gene mutations, but also other disorders can occur.